A Bibliometric Analysis of the Effectiveness of Green Labeling in Enhancing Consumer Value Perceptions - Judijanto, Loso; Didik Widiarta, I Putu Gede; Juliadilla , Risa (Westscience Press, 2025)
Green labeling has emerged as a critical tool for promoting sustainable consumption by signaling a product’s environmental benefits. However, the effectiveness of green labels in enhancing consumer value perceptions remains a subject of debate due to issues such as greenwashing, label proliferation, and consumer skepticism. This study employs a bibliometric analysis using data exclusively from Scopus and analyzed through VOSviewer to systematically map the intellectual structure of research on green labeling and consumer value perceptions. The findings reveal that key research themes include sustainability, green marketing, consumer behavior, purchase intention, and willingness to pay, with a noticeable shift towards consumer-driven sustainability trends in recent years. Co-authorship network analysis indicates that research is dominated by two major clusters—Western scholars focusing on behavioral models and Asian researchers emphasizing corporate sustainability and trust in eco-labels. While green labels positively influence perceived consumer value, their effectiveness is contingent on factors such as label credibility, standardization, and consumer education. Challenges such as eco-label confusion, cost barriers, and inconsistent regulatory enforcement remain pressing concerns. The study highlights the need for standardized regulations, technological integration (e.g., blockchain for label verification), and cross-cultural studies to improve green labeling’s impact. The insights from this research provide a comprehensive understanding of the evolution of green labeling literature, offering practical implications for businesses, policymakers, and researchers seeking to enhance consumer trust in sustainable products.